Systematic identification of pathological mechanisms, prognostic biomarkers and therapeutic targets by integrating lncRNA expression variation in salivary gland mucoepidermoid carcinoma - Yan-ping Zou; Xiao-feng Shan; Jia-xuan Qiu; Yan Geng; Shang Xie; Ruo-lan Xiang; Zhi-gang Cai (Scientific Reports)
Abstract Biological processes intricately intertwine with tumorigenesis, significantly influencing treatment outcomes and prognosis. However, the mechanisms fostering mucoepidermoid carcinoma (MEC) remain inadequately elucidated. This research utilizes expression profiles of lncRNAs from clinical MEC tissues and matched normal glandular tissues, integrating public data to explore the biological mechanisms and immune microenvironment characteristics of tumorigenesis. Gene set enrichment analysis identified key pathways, and a customized epithelial-mesenchymal transition (EMT) score elucidated the relationship between pathological processes and prognosis, while an immune signature revealed tumor microenvironment characteristics. MECs exhibited significant enrichment in EMT pathway, with key genes such as Secretogranin II, tissue factor pathway inhibitor 2, and periostin identified as contributors to the EMT process. High EMT scores correlated with upregulated EMT and immune response activity, indicating poor prognosis. Single-sample gene set enrichment analysis unveiled the tumors’ immune infiltration signature, suggesting active antigen presentation and a positive immune response for immunotherapy. Additionally, SLC2A1-AS1 and CERS6-AS1 were identified as potential mediators of EMT and the immune environment. This study provides insights into the biological processes of MEC tumorigenesis and identifies potential therapeutic targets for future research.